The types of bank that influencing the higher fixed deposit return for MD Tampin / Muhammad Hairee Ismail and Sharifah Zainab Qubra Al Attas - Ismail, Muhammad Hairee; Qubra Al Attas, Sharifah Zainab (Faculty of Business and Management, 2016)
Over the few years, Majlis Daerah Tampin had invested their money in fixed deposit account for their future. This study intends to examine which types of bank giving the higher fixed deposit return for Majlis Daerah Tampin. The data ranges from 2008 to 2016 on a quarterly basis which comprises of 31 observation. There are total of three independent variable which are Commercial Bank Fixed Deposit Return, Merchant Bank Fixed Deposit return and Bank Badan Berkanun Fixed Deposit Return and Company Fixed Deposit Return as dependent variable. In the process of findings, the researcher is using Eviews9 statistical tool to generate all the data for analysis purpose. The result shows that Bank Badan Berkanun as the independent variable has significant relationship towards the Company Fixed Deposit Return. This study is done to contribute and information to Majlis Daerah Tampin for their future investment and to enhance public about the fixed deposit account.